2012
DOI: 10.1186/1758-2555-4-23
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison between single-bundle and double-bundle anterior cruciate ligament reconstruction with hamstring tendon under cyclic loading condition

Abstract: Purpose: The purpose of this study was to compare the anterior tibial translation (ATT) of the anterior cruciate ligament (ACL) reconstructed-knee between single-bundle and double-bundle ACL reconstruction under cyclic loading. Methods: Single-bundle and double-bundle reconstructions of the knee were performed sequentially in randomized order on the same side using eight human amputated knees. After each reconstruction, the reconstructed-knee was subjected to 500-cycles of 0 to 100-N anterior tibial loads usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The repetitive bending or the abrasive force at the sharp femoral tunnel aperture may cause excessive stress on the graft, which can be a possible cause of graft damage or poor healing after ACL reconstruction 40,44,45 . Graft deformation at the femoral aperture corner has been reported after anatomic ACL reconstruction when applying cyclic load to cadavers 46 . Since GBA is affected by intra-articular tunnel apertures and extra-articular tunnel exits, different tunnel locations and orientations created by two kinds of femoral drills can lead to varying GBA.…”
Section: Introductionmentioning
confidence: 99%
“…The repetitive bending or the abrasive force at the sharp femoral tunnel aperture may cause excessive stress on the graft, which can be a possible cause of graft damage or poor healing after ACL reconstruction 40,44,45 . Graft deformation at the femoral aperture corner has been reported after anatomic ACL reconstruction when applying cyclic load to cadavers 46 . Since GBA is affected by intra-articular tunnel apertures and extra-articular tunnel exits, different tunnel locations and orientations created by two kinds of femoral drills can lead to varying GBA.…”
Section: Introductionmentioning
confidence: 99%
“…20,27,33 Repetitive stress and traumatic forces to the ACL graft before biological graft incorporation may contribute to graft failure. 14,16,31 A steep graft bending angle (GBA) has been recently proposed as a biomechanical factor that could contribute to poor graft healing or graft damage. 1,17,30,39,45,50 The GBA is defined as the angle between the femoral bone tunnel and the line connecting the femoral and tibial tunnel apertures.…”
mentioning
confidence: 99%
“…28,37,50 Graft deformation at the femoral aperture corner has been also reported after anatomic ACL reconstruction. 31 Because the GBA is determined by tunnel locations, it is also influenced by the position of the tibia relative to the femur, which is task dependent. Therefore, in vivo, dynamic weightbearing activities can provide a better indication of the GBA that is likely to affect the graft than static examinations.…”
mentioning
confidence: 99%
“…Good knee range of motion and stability are important goals of treatment. Nohmi et al [ 37 ] reported that double-bundle reconstruction could prove more stable throughout knee range of motion than single-bundle reconstruction. To increase the strength of the suture, we used a special suture technique—baseball running cross-stitch—with 2-0 COBRAID (Smith & Nephew) nonabsorbable suture to repair the injured ligaments in situ.…”
Section: Discussionmentioning
confidence: 99%